Transient elastography and controlled attenuation parameter to evaluate hepatic steatosis and liver stiffness in postpartum patients. (31st December 2023) - Hussain, Farrah Naz; Rosenbluth, Emma; Feldman, Kristina Martimucci; Strauss, Tirtza Spiegel; Schneider, Emily; Schmidt-Beauchat, Emily; Rodriguez-Rivas, Clara; Brustman, Lois; Kushner, Tatyana
Abstract: Introduction: Nonalcoholic fatty liver disease (NAFLD) affects 30% of adults in the United States. Transient elastography (TE) (Fibroscan, Echosens, Paris, France) with controlled attenuation parameter (CAP) is a noninvasive way to evaluate liver steatosis and liver stiffness. The primary objective of this study was to assess prevalence of elevated liver stiffness and steatosis immediately postpartum. Furthermore, we sought to evaluate whether there were differences in rates of metabolic disorders of pregnancy (gestational diabetes mellitus (GDM), gestational hypertension, and preeclampsia) and pre-pregnancy conditions (type 2 diabetes mellitus (DM), chronic hypertension, and obesity) in those with elevated postpartum liver steatosis/liver stiffness. Methods: IRB approved prospective cross-sectional study in which TE and liver function tests were performed 1–2 days postpartum. CAP ≥300 dB/m was classified as significant steatosis. Increased liver stiffness was defined as ≥7 kPa. Prevalence was determined by proportion of individuals undergoing TE/CAP who met criteria. Chi-square analysis was used to compare differences between groups. Results: Eighty-nine patients were included: 20 (22%) had GDM, 13 (15%) had gestational hypertension, and 15 (17%) had preeclampsia. Women with kPa ≥7 were more likely to have ALT ≥25, type 2 diabetes, and preeclampsia ( p  < .05). Pre-gravid BMI, BMI at delivery, and GDM were not associated with increased kPa. Pregravid BMI ≥25 and chronic hypertension were associated with CAP ≥ 300 dB/m ( p  < .05). GDM, preeclampsia, and gestational hypertension were not associated with CAP ≥300 dB/m. Conclusions: Patients with preeclampsia, type 2 diabetes, and elevated ALT were more likely to have elevated postpartum liver stiffness. Pregravid BMI ≥25 and ≥30 were associated with increased liver steatosis, although did not impact liver stiffness. GDM was not associated with increased liver stiffness or steatosis. Consideration should be made for screening pregnant patients with preeclampsia, type 2 DM and overweight or obese BMI for liver disease in the postpartum period with potential for lifestyle intervention.